TEORI PERMINTAAN DALAM PERSPEKTIF EKONOMI ISLAM DAN KONVENSIONAL - Haryanti, Nine (Jurnal Ilmu Akuntansi dan Bisnis Syariah (AKSY), 2019)
ABSTRACT Microeconomic theory is one of the branches of science that is very important in society, where people to meet their needs will create demand. Studying from an Islamic and conventional perspective on demand, in general, is almost the same. This study aims to find out how the theory of demand in Islamic and conventional viewpoints. Using a descriptive qualitative method, collecting data by combining from several sources and discussions with students of Islamic economics majoring in Siliwangi University. So, from the results of research on legal sources that are used by Islamic boundaries in view of demand, from the existence of different views about commodities and objectives to be achieved. The main source of the theory of Islamic demand is the Qur'an, al-hadith, and as-sunnah of the Prophet Muhammad. Meanwhile, in conventional theory, human reason is sometimes not even rational when buying a number of commodities for goods or services.